Conformational studies of some small biological molecules and their interactions with metal ions - Russell, Jill Catherine (Department of Chemistry, 2016)
The solid Cu(II) and Co(II) complexes and complex salts of some thiamine analogues have been prepared. Their electronic spectra, I.R. spectra and Magnetic Moments are presented and discussed in terms of suggested coordination geometries for the complexes. In addition the solution conformations of the Gd(III), Dy(III) and Ho (III) complexes of some 3' , 5' cyclic nucleotides were determined quantitatively using NMR line broadening and line shifting techniques. Reactions of Mn(II) with the cyclic nucleotides were used to find the preferred binding sites on the ligands also using line broadening techniques.